Pengaruh Negosiasi Dan Kepercayaan Terhadap Komitmen Organisasi Pegawai Di Kantor Samsat Tulang Bawang Bara - Sri Retnaning Rahayu; Fitriani; Herwin Tipriadi (Universitas Muhammadiyah Metro, 2024)
Negotiation and trust are important factors in employees to form an organizationalcommitment that should be able to exceed targets in achieving organizational goals. So thepurpose of this research is partially and simultaneously to determine the magnitude of thecorrelation of negotiation and trust in organizational commitment in the West TulangBawang Samsat office. The data collection technique uses a questionnaire and a sample sizeof 30 employees. Then the results of the questionnaire data were tested for validity andreliability, which were then tested for normality, linearity, homogeneity and multipleregression of the partial and simultaneous test decisions and the coefficient of determination.The results of the analysis prove that negotiations involving two or more parties with theemployee's self-confidence, the organizational commitment that is formed by each employeeis able to adjust to what he wants in achieving common goals in order to advance aninstitution/organization.